The Development of the 2013 Student Curriculum Book Based on Thinking Actively in Social Context for Elementary School Students - Hamimah Hamimah; Zuryanty Zuryanty; Ary Kiswanto Kenedi; Nelliarti Nelliarti (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThis research was motivated by the necessity of having student books that suit to the 2013 curriculum objectives, the characteristics of elementary school students and the characteristics of learning outcomes. The study aims to develop valid, practical, and effective elementary school student books based on thinking actively in social context. Employing a 4-D research model (define, design, development and disseminate), the data were garnered using tests, questionnaires, observations, interviews and documentation. The data from tests and questionnaires were analyzed using descriptive statistics whereas the triangulation was used to analyze the data collected through observations, interviews, and documentation. The results showed that the developed student books met the valid criteria with a final score of 85.25% (very valid). It was found that the student books are easy to use, time-saving, and useful to implement in the classroom practices. It could also enhance student learning outcomes in terms of spiritual attitudes, social, knowledge and skills with a percentage increase of 15.35%. As those books are valid, practical, and effective; they can be used as a reference for the learning activities in elementary schools.Keywords: student books, 2013 curriculum, TASC, elementary schools.AbstrakPenelitian ini dilatarbelakangi oleh perlunya buku siswa yang selaras dengan tujuan kurikulum 2013, karakteristik siswa sekolah dasar, dan karakteristik hasil belajar. Penelitian ini bertujuan untuk mengembangkan buku siswa kurikulum 2013 berbasis thinking actively in social context untuk sekolah dasar yang valid, praktis, dan efektif. Menggunakan model penelitian 4-D (define, design, development, disseminate), data dikumpulkan mealui tes, angket, observasi, wawancara dan dokumentasi. Data yang diperoleh dari tes dan angket dianalisis menggunakan statistik deskriptif sedangkan triangulasi digunakan untuk menganalisis data yang berasal dari observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa buku siswa yang dikembangkan telah memenuhi kriteria valid dengan skor akhir 85,25% (sangat valid). Buku siswa mudah digunakan, menghemat waktu, dan bermanfaat dalam implementasinya pada pembelajaran di kelas. Buku siswa juga dapat meningkatkan hasil belajar siswa sekolah dasar pada aspek sikap spiritual, sosial, pengetahuan dan keterampilan dengan persentase kenaikan sebesar 15,35%. Karena buku yang telah dikembangkan valid, praktis, dan efektif, buku siswa tersebut dapat dijadikan sebagai rujukan untuk kegiatan pembelajaran di sekolah dasar.Kata kunci: buku siswa, kurikulum 2013, TASC, sekolah dasar.